Pemberian Ekstrak Metanol Akar Pasak Bumi Mempertahankan Bobot Badan Induk Mencit Selama Menyusui (ADMINISTRATION OF EURYCOMA LONGIFOLIA EXTRACTS STABILIZED THE BODY WEIGHT OF LACTATING MICE) - Panjaitan, Ruqiah Ganda Putri; ., Zulfan (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
This research aim is to study the effect of E. longifolia Jack. roots methanol extract and its derivedfraction (n-hexane, chloroform, ethyl acetate, and methanol-water) on body weight of lactating mice. Thetreatment groups were administered 14 mg/20 g body weight of E. longifolia Jack. roots methanol extractand its derived fractions for 21 consecutive days. As a control are without treatment and placebo whichreceived aquadest at dose 0.056 ml/20 g body weight. The administration of E. longifolia Jack rootsmethanol extract showed the smallest change of body weight 29,63 g at the 3rd day and 29,31 g at the 21stday. Compared without treatment and placebo, oral administration of E. longifolia Jack. roots methanolextract and its derived fractions had no significant effects on body weight lactating mice at the 3rd and 21stdays in lactation period (p>0.05). It is concluded that the consumption of E. longifolia Jack. roots methanolextract and its derived fraction during lactation period not influence body weight of lactating mice.
Keywords: Eurycoma longfolia Jack, body weight of lactating mice, lactation period